Dampak kecemasan terhadap pemenuhan pola istirahat tidur pada pasien pre-operasi di ruang rawat inap RSUD Kota Langsa - Kasad Kasad; Azwarni Azwarni; Nora Hayani (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background: Rest and sleep are basic needs of all people. Normally, everyone needs adequate rest and sleep. Factors that influence this pattern are feelings of anxiety. Fear of the unknown and surgical procedures will be the most common cause for inpatients to feel as a form of anxiety.Objectives: Study aims to measure the level of anxiety level relationship with the fulfillment of restful sleep patterns in patients with pre-surgery in the inpatient room of Langsa City Hospital.Methods: The study was used analytic research design with cross sectional approach. The population in this study were all pre-operative patients with a total sample of 43 respondents taken using accidental sampling techniques. Processing is done computerized with the stages of editing, coding, tabulating and cleaning. Data analysis used chi-square test with the desired confidence level of 95%. Research data is presented in tabular and textular forms.Results: Most of the patients (53.5%) had moderate anxiety level and amounted to only 30.2% who experience mild anxiety. Statistically significant correlation (p < 0.05) between the level of anxiety to the fulfillment of restful sleep patterns in patients with preoperative hospitalization diruang Hospital Langsa, with p = 0.001.Conclusion: Anxiety inpatients have a significant impact on fulfilling sleep rest patterns in pre-operative patients in the inpatient room of Langsa City Hospital. Suggestion, it is necessary to provide a specific explanation by nurses about the surgical actions to be performed pre-operative patients.